2018
DOI: 10.1111/add.14243
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol reverses attentional bias to cigarette cues in a human experimental model of tobacco withdrawal

Abstract: Background and AimsCannabidiol (CBD), a non‐intoxicating cannabinoid found in cannabis, may be a promising novel smoking cessation treatment due to its anxiolytic properties, minimal side effects and research showing that it may modify drug cue salience. We used an experimental medicine approach with dependent cigarette smokers to investigate if (1) overnight nicotine abstinence, compared with satiety, will produce greater attentional bias (AB), higher pleasantness ratings of cigarette‐related stimuli and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 63 publications
(79 reference statements)
5
73
1
Order By: Relevance
“…Our results suggest that any reported cannabis use was associated with significantly lower smoking quit ratios, relative to those who did not use cannabis. Cannabidiol has been proposed as a treatment for a number of addictive substances,44 and studies have begun to examine cannabidiol as a method of reducing cigarette smoking 45 46. While these studies, and studies of other cannabinoid agents,47 find promising results for cigarette smoking behaviours, the simple ad hoc use of cannabis in the current sample did not appear to improve cigarette smoking quit ratios.…”
Section: Discussionmentioning
confidence: 61%
“…Our results suggest that any reported cannabis use was associated with significantly lower smoking quit ratios, relative to those who did not use cannabis. Cannabidiol has been proposed as a treatment for a number of addictive substances,44 and studies have begun to examine cannabidiol as a method of reducing cigarette smoking 45 46. While these studies, and studies of other cannabinoid agents,47 find promising results for cigarette smoking behaviours, the simple ad hoc use of cannabis in the current sample did not appear to improve cigarette smoking quit ratios.…”
Section: Discussionmentioning
confidence: 61%
“…As a whole, these data indicate that cannabidiol might improve cognitive performance during nicotine withdrawal through the modulation of inflammation and cell proliferation. Interestingly, preliminary findings in humans show that cannabidiol reduces cigarette consumption (Morgan et al, 2013), and pleasantness of cigarette cues after overnight abstinence (Hindocha et al, 2018a) in tobacco smokers. In contrast, a recent study has shown that acute administration of a single dose of cannabidiol did not improve memory performance in tasks previously shown to be impaired during cigarette abstinence (Hindocha et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a potential usefulness of cannabidiol in tobacco addiction has been shown in recent clinical studies (Morgan et al, 2013;Hindocha et al, 2018a). Thus, cannabidiol administration reduces cigarette consumption in tobacco smokers (Morgan et al, 2013), and the salience and pleasantness of cigarette cues after overnight abstinence in dependent smokers (Hindocha et al, 2018a).…”
Section: Introductionmentioning
confidence: 97%
“…Endocannabinoid signaling is terminated by enzymes such as FAAH. FAAH inhibition is a mechanism that is currently being investigated as a treatment of CUD in humans . The rs324420 single‐nucleotide polymorphism (SNP) of the FAAH enzyme is a C‐to‐A polymorphism, which results in a proline to a threonine substitution at codon 129.…”
Section: Introductionmentioning
confidence: 99%
“…We focused upon three endophenotypes of CUD, which are distinct but related processes. Firstly, attentional processing is an important transdiagnostic marker for depression, anxiety, and drug dependence . THC‐to‐CBD ratio predicts attentional bias to cannabis cues when intoxicated, with those using more CBD in their cannabis strains showing reduced attentional bias .…”
Section: Introductionmentioning
confidence: 99%